Agronomic bio-fortification of rice by inorganic and organic sources of nutrients - Mangat Ram; Kiran Khokhar; Rajender Garhwal (Annals of Agricultural Research, 2022)
Field investigations on rice crop were carried out during kharif season of 2013 and 2014 to find out the effect of various inorganic and organic sources of nutrients on extent of enrichment of rice with micronutrients Zn and Fe. The treatments consisted of two rice varieties and five enrichment treatments consisting of various inorganic and organic sources of nutrients. Soil application of Zn and foliar application of Fe through inorganic sources significantly increased the concentration of both the nutrients in grains (brown rice) as well as in straw over their no application. The varieties did not differ with respect to their micronutrient concentration but uptake of both the nutrients was higher in HKR 127. The content of both the nutrients further increased with the use of FYM or cytokinein along with the inorganic sources. The highest Zn concentration in grain was achieved when inorganic sources were supplemented with either FYM or cytokinin whereas grain Fe concentration was the highest when both FYM and cytokin in were applied along with the inorganic sources. The effect of various enrichment treatments on uptake of both the micronutrients was similar to that on their concentration. Most of the nutrients absorbed by the crop were retained in straw (73.5% Zn and 70% Fe) with variety HKR 47 retaining more Zn in its grains (28.4%) than HKR 127 (24.6%). It was concluded that in addition to supply of Zn and Fe to the crop through inorganic means, it is necessary to apply either FYM or cytokinin for enrichment of rice grain with Zn whereas addition of both FYM and cytokinin is needed for enrichment with Fe.